러시아 소비자의 한국산 감귤 선호도 분석 - 김경필 (한국농촌경제연구원, 2011)
Russia is an emerging market for Korean fruits and one of the biggest Korean mandarin importers. The purpose of this paper is to analyze the consumers' preference for Korean mandarin in the Russian market. The Russian market is divided into two regions and studied, Vladivostok and Moscow. Field and survey researches were conducted to investigate the market and consumers' behaviors. A conjoint analysis was also conducted to define the consumers' preference for commodity attributes of Korean mandarin. The results of analysis provide the basic information needed to make commercialization and marketing strategies to expand the market share of Korean mandarin in the Russian market.
Keywords: 한국산 감귤; 소비자 선호; 컨조인트 분석; 마케팅; 수출; Korean mandarin; consumers' preference; conjoint analysis; marketing; export